Assessment of Osteoporosis Preventive Lifestyle and Awareness in 13-15-Year-Old Students in Garmsar City in 2018 - Sareh Shakerian; Maryam Fallahi (International Journal of School Health, 2020)
Background: Known as a health and medical problem in the community, osteoporosis (OP) is the most prevalent metabolic bone disease. The most facile approach to dealing with osteoporosis is prevention and lifestyle modification. In adolescents, in particular, lifestyle plays the most important role in preventing from osteoporosis in the adulthood. This study was conducted to determine the level of osteoporosis preventive lifestyle and awareness among 13-15-year-old students in Garmsar city in 2018. Methods: This descriptive cross-sectional study was conducted on 400 high school students selected by two-stage cluster sampling method in Garmsar city in 2018. The data were collected with a three-part questionnaire containing 38 questions related to personal data and measurement of the awareness and lifestyle dimensions associated with osteoporosis prevention, including habits (smoking cigarettes and hookah and exposure to the sun to mention a few), nutrition, and physical activity. Cronbach’s alpha of awareness (0.84), habits (72. 5), and nutrition (0.72) was calculated to specify the reliability of the tool and the content validity was calculated with Lawshe method containing CVR (0.9) and CVT (0.86). For data analysis, use made of descriptive statistics and multiple linear regression by SPSS software version 24. Results: The results of awareness dimension with merely 42.77% correct answers indicated the low awareness of students. The dimension of habits in the preventive lifestyle was in optimal condition with a score of 61.1%. With scores of 33.4 and 25.2%, physical activity and activity without mobility were optimum (score: 70%). There was a direct and significant correlation between students’ awareness and their performance regarding osteoporosis (P<0.05). A direct correlation was further observed between awareness and lifestyle (r=0.255). Conclusions: The studied population had inadequate awareness and poor lifestyle. Given the existing risk factors, it is necessary to pay close attention to education and lifestyle changes in adolescents and their families.